2015
DOI: 10.1177/1533034614566993
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampus-Sparing Whole-Brain Radiotherapy and Simultaneous Integrated Boost for Multiple Brain Metastases From Lung Adenocarcinoma

Abstract: In this study, the volume response and treatment outcome after hippocampus-sparing whole-brain radiotherapy (HS-WBRT) with simultaneous integrated boost (SIB) using tomotherapy were evaluated. Patients with primary lung adenocarcinoma and multiple brain metastases who had a Karnofsky performance status !70 and exhibited well-controlled extracranial disease were treated. The prescribed dose was administered in 10 to 14 fractions as 25 to 28 Gy to whole-brain parenchyma, as 40 to 48 Gy to the gross metastatic le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
(38 reference statements)
1
15
0
Order By: Relevance
“…After a median follow-up of 14 months, a complete remission was observed in 33 % of lesions and a partial response in 45 % with a 65 % reduction of tumor volume. The paper did not report any data about neurocognitive functions [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After a median follow-up of 14 months, a complete remission was observed in 33 % of lesions and a partial response in 45 % with a 65 % reduction of tumor volume. The paper did not report any data about neurocognitive functions [32].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to reduce this potential risk, some experiences evaluated hippocampal sparing during WBRT-SIB, using different arc therapies [14,17,[31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…The RTOG 0212 trial compared patients who received lower dose PCI (25 Gy in 10 fractions, EQD2 26.04 Gy) vs. higher dose PCI (36 Gy in 18 fractions, EQD2 36 Gy or twice-daily 24 fractions, EQD2 34.50 Gy), and showed significant increase of chronic neurotoxicity in the higher dose PCI group [26]. In addition, with advances in technology, especially hippocampus-sparing IMRT, WBRT with lower neurotoxicity is becoming more feasible [27-29]. Some studies have reported that the hippocampus shows radiation dose-dependent atrophy and that hippocampus-saving WBRT is related with preservation of memory and quality-of-life [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…HS-WBRT has been shown to be feasible by multiple groups, with or without integrated boost using linear accelerator-based multi-field IMRT [ 24 ], Volumetric Modulated Arc Therapy (VMAT) [ 25 – 27 ] or Tomotherapy techniques [ 28 ]. Specific IMRT techniques have been recommended and used in the RTOG 0933 trial [ 24 ].…”
Section: Discusssionmentioning
confidence: 99%